2012
DOI: 10.2527/jas.2011-4791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the activity of mitochondrial respiratory chain complexes and feed efficiency in fat-tailed Ghezel lambs1

Abstract: This study was conducted to investigate relationships between mitochondrial respiratory chain complex activities, feed efficiency, and carcass traits in sheep. A group of Ghezel male lambs sired by a single ram were randomly allotted to individual pens. The lambs were fed ad libitum with a fattening diet containing 30% roughage (corn silage and alfalfa hay) and 70% concentrate for 70 d to individually phenotype each lamb for feed conversion ratio (FCR), adjusted FCR (aFCR), and residual feed intake (RFI). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
4
20
0
5
Order By: Relevance
“…the gut has a very rapid turnover) is not known. It is interesting to note that comparing high-and low-feed efficiency or residual feed intake (RFI) in sheep (Sharifabadi et al 2012) indicates reduced mitochondrial respiration in muscles from the more efficient animals. This appears to involve reduced BMR and is associated with genes encoding mitochondrial proteins, suggesting that oxidative metabolism and/or efficiency of ATP synthesis may be key.…”
Section: Energy Balancementioning
confidence: 99%
“…the gut has a very rapid turnover) is not known. It is interesting to note that comparing high-and low-feed efficiency or residual feed intake (RFI) in sheep (Sharifabadi et al 2012) indicates reduced mitochondrial respiration in muscles from the more efficient animals. This appears to involve reduced BMR and is associated with genes encoding mitochondrial proteins, suggesting that oxidative metabolism and/or efficiency of ATP synthesis may be key.…”
Section: Energy Balancementioning
confidence: 99%
“…Since these studies relating mitochondrial parameters to feed efficiency traits were reported, other authors have continued research into the sub-cellular network contributing to economically important production traits in laboratory and livestock species. Sharifabadi et al (2012) were able to study the activities of the various mitochondrial complexes and relate them to different feed efficiency traits in fat-tailed Ghezel lambs. For this study, 25 lambs from the same sire were placed on a feed intake trial and were grouped according to high and low RFI and high and low FCR.…”
Section: The Role Of Mitochondrial Components In Maintenance Requiremmentioning
confidence: 99%
“…After analyzing the RFI group it was determined that low RFI lambs had greater activity at all 5 membrane complexes studied. When analyzing the FCR group they determined that low FCR lambs had greater activity at complexes III, IV, and V. Sharifabadi et al (2012) noted that including information about mitochondrial complexes may be useful to breeding programs selecting animals for feed efficiency. from all 3 replicates of Generation 58 were analyzed.…”
Section: The Role Of Mitochondrial Components In Maintenance Requiremmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play important roles in many biological processes, including fatty acid metabolism, amino acid metabolism, and steroidogenesis [275]. Importantly, mitochondrial function has been associated with feed efficiency in poultry, cattle and lambs [276,277]. As well, it has been shown that the mitochondrial proteome profiles are different between these low and high RFI lines of pigs and the mitochondria from the liver and LD muscle of the low RFI pigs produced less ROS [149][150][151].…”
Section: Potential Relationship Of the Degs And Differentially Co-expmentioning
confidence: 99%